Critical Thinking in the EFL Classroom: The Search for a Pedagogical Alternative to Improve English Learning - Pineda Báez, Clelia (Íkala, Revista de Lenguaje y Cultura, 2004)
This article reports the results of a research study that was undertaken by a group of teachers working in the English program ascribed to the School of Education at Universidad Externado de Colombia, with the financial support of COLCIENCIAS. Tasks related to critical thinking were designed and implemented with three groups of students. A qualitative interpretative case study was conducted to examine how students constructed meaning when dealing with the tasks, the meta-cognitive processes involved in the process, the types of interactions built around the tasks and how they influenced language competence and critical thinking. The findings indicate that language competence and criticality are on-going, never-ending processes. However, teachers can refine them through thought-provoking, stimulating materials. Received: 31-05-04/ Accepted: 17-08-04 How to reference this article: Pineda Báez, C. (2004). Critical Thinking in the EFL Classroom: The Search for a Pedagogical Alternative to Improve English Learning. Íkala. 9 (1), pp. 45 – 80